A Comprehensive Retrospective Analysis in Understanding Covid-19 : Forensic Perspective from a Single Institute - Mary , Sowjanya G; Devaraju , G; Venugopal , Rao G (Journal of Indian Academy of Forensic Medicine, 2023)
SARS-CoV-2 has spread swiftly and disseminated as a pandemic globally. As there was limited research on non-autopsy findings, a detailed analysis of facts gathered from the deceased can aid in a better understanding of the covid disease. The current retrospective cross sectional study was conducted on the 388 probable COVID-19 fatalities, in the department of Forensic Medicine and Toxicology, between st August 1 2020 to August 1st, 2021. Deaths were more common in the age group of 41-60 years with male predominance with greater number being in the Prevaccination period. 74% reported cough, 85% shortness of breath, 88% had fever and anosmia in very few cases. Co-morbidities observed were 18% of hypertension, 16% diabetes and 8% chronic renal disease. Common reasons being respiratory failure due to bilateral pneumonia followed by multi-organ failure and cardiac arrest. Comorbidities added to severity and vaccination has shielding effect in the prevention of deaths.